ALTERNATIVE DA'WAH AND THE VISUALIZATION OF MODERATE ISLAM ON INFOGRAPHICS - Zumala, Zulfi (IAI Darussalam, 2022)
Abstract: Instagram is one of the currently popular social media among many people, especially young generations. Instagram was launched in October 2011 and immediately became viral for photo sharing. Infographics are one way to visualize much complex information into one image uploaded on Instagram application. Infographics are popularly used by many Instagram accounts of Islamic community to inform moderate Islam. This study aims to analyze infographics used by three Instagram accounts, namely @islamidotco, @mubaadalah, and @santrijagad. The circuit of culture theory by Gay (2007) was employed to analyze the infographics of the three accounts. This research is descriptive qualitative research, it is going to investigate how an infographic possibly became an alternative da'wah to visualize moderate Islamic narratives on Instagram platform and how moderate Islamic narratives through infographics were constructed. The second is how non-language patterns used in infographics reflect the uniqueness of moderate Islamic ideology accounts. Besides investigating the infographic contents, readers’ responses on the comment columns are also investigated. The results reveal that the analysed accounts discuss three major issues: @islamidotco focuses on infographics visualizing tolerance, @mubaadalah more focuses on Islam’s efforts to provide justice in relationship, especially, between men and women, and @santrijagad focuses on uploading Islamic scholars’ quotes that deliver friendly and moderate Islamic ideas.